Altered auditory brainstem responses are post-acute sequela of SARS-CoV-2 (PASC) - Christopher Niemczak; Erika Skoe; Samantha Leigh; Linda Zhang; Megan Dotzenrod; Annalise Kieley; Simon Stone; Jeffrey Parsonnet; Christina Martin; Christin Ealer; Odile Clavier; Jiang Gui; et al. (Scientific Reports)
Abstract The Post-acute Sequela of SARS-CoV-2 (PASC) syndrome, also known as Long-COVID, often presents with subjective symptoms such as brain fog and cognitive fatigue. Increased tinnitus, and decreased hearing in noise ability also occur with PASC, yet whether auditory manifestations of PASC are linked with the cognitive symptoms is not known. Electrophysiology, specifically the Auditory Brainstem Response (ABR), provides objective measures of auditory processing. We hypothesized that ABR findings would be linked to PASC and with subjective feelings of cognitive fatigue. Eighty-two individuals, 37 with PASC (mean age: 47.5, Female: 83%) and 45 healthy controls (mean age: 38.5, Female: 76%), were studied with an auditory test battery that included audiometry and ABR measures. Peripheral hearing thresholds did not differ between groups. The PASC group had a higher prevalence of tinnitus, anxiety, depression, and hearing handicap in addition to increased subjective cognitive fatigue. ABR latency findings showed a significantly greater increase in the wave V latency for PASC subjects when a fast (61.1 clicks/sec) compared to a slow click (21.1 clicks/sec) was used. The increase in latency correlated with cognitive fatigue scores and predicted PASC status. The ABR V/I amplitude ratio was examined as a measure of central gain. Although these ratios were not significantly elevated in the full PASC group, to minimize the cofounding effect of age, the cohort was median split on age. Elevated V/I amplitude ratios were significant predictors of both predicted PASC group classification and cognitive fatigue scores in the younger PASC subjects compared to age-matched controls providing evidence of elevated central gain in younger individuals with PASC. More frequent tinnitus also significantly predicted higher subjective cognitive fatigue scores. Our findings suggest that PASC may alter the central auditory pathway and lead to slower conduction and elevated auditory neurophysiology responses at the midbrain, a pattern associated with the typical aging process. This study marks a significant stride toward establishing an objective measure of subjective cognitive fatigue through assessment of the central auditory system.